+0

# first principal

0
412
2

use first principal to find the derivative of

f(x)=sin^2(2x)

\(f(x)=sin^2(2x)\)

Guest Feb 13, 2016

#2
+78551
+5

Note that :

sin^2(2x)   = [1 - cos(4x)]/ 2     ......so we have.....

[ 1 - cos4(x + h)] / 2] * [ 1/h]    -    [1 - cos(4x)] / 2 * [ 1/h ] =

[1 - cos(4x + cos4h)] / 2h   - [1 - cos(4x)] 2h  =

[cos(4x)  -  cos(4x + 4h) ] / 2h   =

[ cos(4x)  - [cos4xcos4h  - sin4xsin4h] ] / 2h  =

[ cos4x ][1 - cos4h] / 2h    +  sin4xsin4h/ 2h        [multiply top/bottom of both fractions by 2]

[2cos4x] [(1 - cos4h) / 4h ] +   [2sin4x] [sin4h/ 4h ]       let h →  0

[2cosx * 0]  +  [2sin4x * 1 ]  =

2sin4x  =

2sin(2x + 2x)  =

2[ sin2xcos2x + sin2xcos2x]  =

2 [ 2 * sin2xcos2x]  =

4[sin2x] [cos2x]

-------------------------------------------------------------------------

Note that :   [sin(2x)]^2  =  [sin2x ] * [sin2x]     (1)

And using the Product Rule, the derivative  of (1)  =

[2cos2x] [sin2x] + [sin2x][ 2 cos2x]  =

[2cos2x] [ sin2x + sin2x]  =

[2cos2x] [2sin2x] =

4[sin2x][cos2x]

CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
Sort:

#1
+5

Find the derivative of the following via implicit differentiation:

d/dx(f(x)) = d/dx(sin^2(2 x))

The derivative of f(x) is f'(x):

f'(x) = d/dx(sin^2(2 x))

Using the chain rule, d/dx(sin^2(2 x)) = ( du^2)/( du) ( du)/( dx), where u = sin(2 x) and ( d)/( du)(u^2) = 2 u:

f'(x) = 2 d/dx(sin(2 x)) sin(2 x)

Using the chain rule, d/dx(sin(2 x)) = ( dsin(u))/( du) ( du)/( dx), where u = 2 x and ( d)/( du)(sin(u)) = cos(u):

f'(x) = cos(2 x) d/dx(2 x) 2 sin(2 x)

Factor out constants:

f'(x) = 2 d/dx(x) 2 cos(2 x) sin(2 x)

Simplify the expression:

f'(x) = 4 cos(2 x) (d/dx(x)) sin(2 x)

The derivative of x is 1:

f'(x) = 1 4 cos(2 x) sin(2 x)

Simplify the expression:

f'(x) = 4 cos(2 x) sin(2 x)

Expand the left hand side:

Answer: |f'(x) = 4 cos(2x) sin(2x) =f'(x) = 2 sin(4x)

Guest Feb 13, 2016
#2
+78551
+5

Note that :

sin^2(2x)   = [1 - cos(4x)]/ 2     ......so we have.....

[ 1 - cos4(x + h)] / 2] * [ 1/h]    -    [1 - cos(4x)] / 2 * [ 1/h ] =

[1 - cos(4x + cos4h)] / 2h   - [1 - cos(4x)] 2h  =

[cos(4x)  -  cos(4x + 4h) ] / 2h   =

[ cos(4x)  - [cos4xcos4h  - sin4xsin4h] ] / 2h  =

[ cos4x ][1 - cos4h] / 2h    +  sin4xsin4h/ 2h        [multiply top/bottom of both fractions by 2]

[2cos4x] [(1 - cos4h) / 4h ] +   [2sin4x] [sin4h/ 4h ]       let h →  0

[2cosx * 0]  +  [2sin4x * 1 ]  =

2sin4x  =

2sin(2x + 2x)  =

2[ sin2xcos2x + sin2xcos2x]  =

2 [ 2 * sin2xcos2x]  =

4[sin2x] [cos2x]

-------------------------------------------------------------------------

Note that :   [sin(2x)]^2  =  [sin2x ] * [sin2x]     (1)

And using the Product Rule, the derivative  of (1)  =

[2cos2x] [sin2x] + [sin2x][ 2 cos2x]  =

[2cos2x] [ sin2x + sin2x]  =

[2cos2x] [2sin2x] =

4[sin2x][cos2x]

CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016
edited by CPhill  Feb 13, 2016

### 23 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details